Measuring The Effectiveness Of Summons And Notification By Registered Mail In Civil Cases At The Denpasar District Court - Diah Yustiasari; Ni Ketut Wiratny; Erikson Sihotang (PT Publikasiku Academic Solution, 2024)
The summons and notification process in civil cases is a very important initial stage in resolving disputes in court. An illegal summons or inappropriate notification can result in the decision being annulled or even delaying the judicial process, which is certainly detrimental to the parties to the dispute. In Indonesia, especially at the Denpasar District Court, one of the methods used for summons and notification is by registered letter. This method was chosen because it is considered more formal and has reliable proof of delivery. However, the effectiveness of using registered letters as a means of summons and notification in civil cases needs to be evaluated. This is important to ensure that this method can actually achieve its objective, namely providing valid and timely notification to the parties to the dispute. The effectiveness of this method will have a direct impact on the smooth running of the judicial process and legal certainty for the parties involved. This research was conducted both empirically and normatively research to find the effectiveness of using registered letters as a way to summon litigants in civil cases at the Denpasar District Court. The facts obtained on the ground are that many court summons are not properly delivered to the litigants, and then court summons that failed to be sent will be returned to the Denpasar District Court without a stamp from the Village Chief as required by the provisions. In this case, evaluation is needed from both parties, the Denpasar District Court and PT Pos Indonesia, so that the summons and notification via registered letter can be carried out effectively and by applicable regulations.